(untitled) - Anthropos Institut e.V. (Anthropos, 2023)
Anthropos is the international journal of anthropology and linguistics, founded in 1906 by Wilhelm Schmidt, missonary and member of the Society of the Divine Word (SVD). Its main purpose is the study of human societies in their cultural dimension. In honor of Wilhelm Schmidt‘s legacy, the cultivation of anthropology, ethnology, linguistics, and religious studies remain an essential component oft he Anthropos Institute – the organizational carrier of the journal.